Method of Measurement Representativeness Assessment for Spatial Conductometric Sensors as Applied to Investigation of Hydrodynamics in Single Phase Flows - A. A. Barinov; V. G. Glavny; S. M. Dmitriev; M. A. Legchanov; A. V. Ryazanov; A. E. Khrobostov (Приборы и методы измерений, 2018)
The well-known method of spatial conductometry is widely used for hydrodynamical investigations in the frame of validation benchmarks. The aim of the work was to develop the method of representativeness substantiation for use of the conductometric sensors in single-phase applications.The paper presents aspects of wire-mesh sensors (WMS) applications in non-uniform conductivity fields. The equivalent electrical circuits for the measurement cell and WMS are proposed and investigated. The methods of translation from measured conductance to conductivity of the water are discussed. Decomposition of the uncertainty sources and their propagation through measurements are investigated.To obtain the «cross-talk» effect of the measurements the fi model of WMS fl domain was created. The results of calculations showed the dependence of the measurement results on the conductivity contrast in the cells as well as on the size of the contrast domain. The proposed method of the measurement uncertainty estimate was applied to the real WMS and it’s measurement system. The obtained results are topical for validation tests with the use of tracer methods and WMS.